Abortion-prone mating influences placental antioxidant status and adversely affects placental and foetal development. (December 2014) - Al-Gubory, K. H.; Krawiec, A.; Grange, S.; Faure, P.; Garrel, C.
Abstract Oxidative stress is associated with decreased female fertility and adversely affects prenatal development. Mammalian cells have developed a network of enzymatic and non-enzymatic antioxidant defence systems to prevent oxidative stress. Little attention has been paid to the antioxidative pathways in placentas of normal and disturbed pregnancies, leaving a gap in our knowledge about the role of antioxidants in the control of foeto-placental development. The challenges in studying early human pregnancy can partly be overcome by designing animal models of abnormal pregnancy. We aimed to determine whether the antioxidant status of placentas from the CBA/J × DBA/2 abortion-prone pregnant mice differed from that of normal pregnant mice. The foetal/placental weight ratio was lower in abortion-prone matings compared with that in non-abortion-prone matings. The increased placental malondialdehyde (MDA) content, the end products of lipid peroxidation, with concomitants alterations in placental antioxidants, namely copper-zinc containing superoxide dismutase (SOD1), manganese containing (SOD2), glutathione peroxidases (GPX), glutathione reductase (GR) and catalase (CAT) activities may be involved in placental and foetal growth restriction. We show that placental oxidative stress is linked with poor prenatal development and pregnancy losses in CBA/J × DBA/2 mice matings. This animal model may be useful in the evaluation of nutritional antioxidant therapies for oxidative stress and associated prenatal developmental disorders.